Linking thermal imaging and soil remote sensing to enhance irrigation management of sugar beet. (January 2018) - Quebrajo, L.; Perez-Ruiz, M.; Pérez-Urrestarazu, L.; Martínez, G.; Egea, G.
Abstract : The use of reliable information and data that are rapidly and easily acquired is essential for farm water management and appropriate irrigation strategies. Over the past decade, new advances have been made in irrigation technology, such as platforms that continuously transmit data between irrigation controllers and field sensors, mobile apps, and equipment for variable rate irrigation. In this study, images captured with a thermal imaging camera mounted on an unmanned aerial vehicle (UAV) were used to evaluate the water status of sugar beet plants in a plot with large spatial variability in terms of soil properties. The results were compared with those of soil moisture measurements. No direct relationship was observed between the water status of the soil and that of the crops. However, the fresh root mass and sugar content tended to decrease when higher levels of water stress were detected in the crop using thermal imaging, with coefficients of determination of 0.28 and 0.94 for fresh root mass and sugar content, respectively. Differences were observed between different soil types, and therefore different irrigation strategies are needed in highly heterogeneous plots. Highlights: Precision irrigation is useful when is a high soil variability. Thermal imaging was validated to obtain canopy temperature. Micro-UAV platform with a thermal camera used for water stress detection. Decision support tool for the efficient irrigation management of sugar beet.